(untitled) (Fiep Bulletin - online, 2013)
Technological innovations have brought comfort and facilities for all persons requiring major obstacles to maintainingadequate levels of physical activity, favoring an increase in sedentary population. The purpose of this descriptive study was toevaluate the usual time of virtual social networks and physical fitness of 71 students of both sexes, aged between 15 and 16 yearsenrolled in the 1st and 2nd year of high school of the College Mater Christi, users of virtual social networks (Twiter, Msn,Facebook, Orkuts) in the city of Mossoró-RN. As an instrument of data collection were used: a questionnaire to identify thefrequency usual social networks, with a balance of stadiometer Sanny (weight and height) to evaluate the anthropometricindicators. The analyzed data allow us to conclude that the majority of social networking users stay connected on Facebook for adaily period 1-3 hours. While most teenagers are experiencing the normal body mass index, shows up a level of physical fitnesstoo weak